2016
DOI: 10.3389/fpls.2016.00116
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Mechanisms of Seed Priming-Induced Chilling Tolerance in Rice Cultivars

Abstract: Rice belongs to tropical and subtropical environments and is extremely sensitive to chilling stress particularly during emergence and early stages of seedling development. Seed priming can be a good approach to enhance rice germination and stand establishment under chilling stress. The present study examined the role of different seed priming techniques viz., hydropriming, osmopriming, redox priming, chemical priming, and hormonal priming, in enhancing the chilling tolerance in rice. The most effective reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
173
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(195 citation statements)
references
References 55 publications
(80 reference statements)
18
173
2
2
Order By: Relevance
“…ROS are chemically aggressive, and attack the polyunsaturated fatty acid components of membrane lipids, resulting in lipid peroxidation (Shah et al, 2001). This process results in the disruption of the physical and functional properties of membranes (Hussain et al, 2016). In the present study, 'Liangyoupeijiu' had lower levels of lipid peroxidation than the control plants at low temperature, while cold stress resulted in higher lipid peroxidation levels in 'Shanyou63'.…”
Section: Discussionsupporting
confidence: 39%
“…ROS are chemically aggressive, and attack the polyunsaturated fatty acid components of membrane lipids, resulting in lipid peroxidation (Shah et al, 2001). This process results in the disruption of the physical and functional properties of membranes (Hussain et al, 2016). In the present study, 'Liangyoupeijiu' had lower levels of lipid peroxidation than the control plants at low temperature, while cold stress resulted in higher lipid peroxidation levels in 'Shanyou63'.…”
Section: Discussionsupporting
confidence: 39%
“…Seed-priming of wheat with salicylic acid (SA) increased moisture content, dry matter yield, antioxidant activity and total chlorophyll content under drought stress (Singh and Usha, 2003), and selenium (Se) priming was reported to enhance drought tolerance in rapeseed by regulating enzymatic and non-enzymatic antioxidant activities (Hasanuzzaman and Fujita, 2011). Recently, seed-priming with selenium (Se) and SA was reported to be more effective in protecting rice plants against chilling stress (Hussain et al, 2016b). Thus, seed-priming with plant hormone and chemical compound is found to be effective in assuaging the damaging effects of abiotic stress in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the growth performance of hybrid maize was better than inbred cultivars under control as well as stress conditions (Figure 1,2 and 3). Early season drought coupled with chilling stress limited seed germination and early stand establishment that may be due to reduced intake of water during seed imbibition [4,18,19,21]. Drought and chilling-induced reductions in morphological traits of maize have also been reported previously [4,9,21].…”
Section: Discussionmentioning
confidence: 70%
“…Osmo-regulation by accumulation of different osmolytes plays significant role in turgor maintenance and protection of macromolecules in dehydrating cells under stressful conditions [15,16]. In order to control the overproduction of ROS, the plants have a highly efficient and sophisticated enzymatic and non-enzymatic antioxidative defense system [1,18,19]. Guo et al (2006) reported that drought and chilling tolerance in plants is strongly linked with the enhanced activities/levels of antioxidants under stress condition [20].…”
Section: Introductionmentioning
confidence: 99%